The Importance of Nutrition Before and Following Metabolic/Bariatric Surgery - Halit Tanju Besler; Esila Bayar (Trends in Surgical Sciences, 2025)
Obesity is a chronic disease, a global epidemic and among the non-communicable disease targets which are identified by World Health Organization (WHO). Bariatric surgery (BS) is one of the treatment approaches used in the fight against obesity. In this article, it is aimed to present general information about BS, nutritional evaluation before and after BS, various nutrition-related conditions, and information on how food supplements and diet phases should be maintained. In addition, factors that should be taken into consideration in individuals undergoing BS and new approaches in BS are included. BS has different methods, such as restrictive and malabsorptive methods. The process before and after BS differs. It is important to evaluate and follow up on an individual basis in a multidisciplinary way. BS methods may have an effect on the absorption of nutrients and the food intake may not meet the requirement due to anatomical changes after surgery. Therefore, food supplements should be given based on the need. In addition, an individual's diet should progress in stages. Considering the risk factors of individuals with BS, postoperative body weight loss should be maintained in the healthiest way. In order to use BS as an effective tool in obesity management, it is considered necessary to develop solutions for the risk factors carried by the individuals who constitute the target group for BS, to manage and maintain the process and follow-up in the most ideal way.